Women in literary production: A bibliometric analysis in the books of the Coronado Collection - Ledesma, Gretel Alvarez; Peralta-González, María Josefa (Advanced Notes in Information Science, 2023)
The books from the Coronado Collection were analyzed from a gender bibliometric perspective. This study has a predominant quantitative approach based on collecting and analyzing quantitative data to characterize the genre of the Coronado Collection. Bibliometric indicators focused on gender were applied to the works' authorship, themes, and titles. This made it possible to verify that the documentary collection is characterized by male predominance in most of its variables and reflects female discrimination in a high percentage of the works that compose it. The existence of recognized female figures was demonstrated, highlighting the historical and social value of the Collection due to its imprint on Cuban culture and the role of women within society. This is the first study that results in the description of the collection of books from the Coronado Collection with a gender focus and from a bibliometric perspective.